NATURE USAGE OF HYDRO RESOURCES IN THE REPUBLIC OF CRIMEA - Inessa Penkova; Lyudmila Akinina (Вестник Северо-Кавказского федерального университета, 2022)
The article aims at determining the key features of the nature usage of hydro resources in the reproduction and health purposes in the Republic of Crimea. It has caused the need to investigate the current situation in the field of nature management of hydro resources for reproduction and recreation purposes in the Republic of Crimea. The authors present a functional analysis of the legislatively established structure of the state regulation within water usage sphere in the Crimea. The material analyzes the financing of water use in the territory of the Crimea with an emphasis on reproductive and recreational features of the Crimean hydro resources. The study has identiied the main problems of nature management sustainability in the ield of reproductive and recreational water resources, which has allowed to formulate the main directions for solution ofproblems found.